Therapeutic Effect of Ilex hainanensis Merr. Extract on Essential Hypertension: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yang, Xiaochen; Yang, Guoyan; Li, Weina; Zhang, Yun; Wang, Jie (Frontiers in Pharmacology, 2018)
With a rapidly aging population, the prevalence of hypertension in adults continues to rise, placing a substantial and escalating social and economic burden. Ilex hainanensis Merr. is commonly used as a folk remedy for treating hypertension, dyslipidemia and inflammation in China. This systematic review aims to evaluate current evidence for the therapeutic effect of Ilex hainanensis Merr. extract (EIH) on essential hypertension. Six electronic databases (Pubmed, MEDLINE, The Cochrane Central Register of Controlled Trials, Chinese Scientific Journals Database, Wanfang and CNKI) were searched to identify eligible randomized controlled trials (RCTs) relevant to EIH on essential hypertension up to Jan 2018. Six RCTs including 772 participants met eligibility criteria. Methodological quality of the trials was generally low. Meta-analysis showed that EIH demonstrated a beneficial effect for lowering systolic and diastolic blood pressure (SBP/DBP), left ventricular mass (LVM) in participants with essential hypertension. There was no significant difference between EIH and antihypertensive drugs in SBP (WMD: -0.44 [-2.30, 1.43]; P =0.65), DBP (WMD: WMD: -0.02[-1.13, 1.09]; P =0.98) and LVM (WMD: -1.36 [-4.99, 2.26]; P =0.46). Moreover, one trial showed that EIH combined with antihypertensive drugs was more effective in lowering blood pressure than those antihypertensive drugs used alone. However, the findings were limited by the small sample sizes, duration and low methodological quality of the trials. This is the first systematic review of EIH on essential hypertension. More rigorous RCTs with high quality are still needed to prove the effectiveness and safety of EIH and its preparations for essential hypertension.